Joint-angle specific strength adaptations influence improvements in power in highly trained athletes - Rhea, M. R.; Kenn, J. G.; Peterson, M. D.; Massey, D.; Simmo, R.; Marin, P. J.; Favero, M.; Cardozo, D.; Krein, D. (Human Movement, 2016)
Purpose. The purpose of this study was to examine the influence of training at different ranges of motion during the squat exercise on joint-angle specific strength adaptations. Methods. Twenty eight men were randomly assigned to one of three training groups, differing only in the depth of squats (quarter squat, half squat, and full squat) performed in 16-week training intervention. Strength measures were conducted in the back squat pre-, mid-, and post-training at all three depths. Vertical jump and 40-yard sprint time were also measured. Results. Individuals in the quarter and full squat training groups improved significantly more at the specific depth at which they trained when compared to the other two groups (p < 0.05). Jump height and sprint speed improved in all groups (p < 0.05); however, the quarter squat had the greatest transfer to both outcomes. Conclusions. Consistently including quarter squats in workouts aimed at maximizing speed and jumping power can result in greater improvements.